2017
DOI: 10.1016/j.jconrel.2016.12.035
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and facile quantitation of polyplex endocytic trafficking

Abstract: Design of safe and effective synthetic nucleic acid delivery vectors such as polycation/DNA or polycation/siRNA complexes (polyplexes) will be facilitated by quantitative understanding of the mechanisms by which such materials escort cargo from the cell surface to the nucleus. In particular, the mechanisms of cellular internalization by various endocytosis pathways and subsequent endocytic vesicle trafficking have been shown to strongly affect nucleic acid delivery efficiency. Fluorescence microscopy and subce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
1
6
0
Order By: Relevance
“…As early as 20–30 min, fluorescently labeled PBA copolymers were mostly internalized (Figure A) and colocalized with LysoTracker, a marker of lysosomes (Figure B). This is consistent with other studies reporting that polycationic materials rapidly traffic into acidic compartments as early as 5 min, with greater trafficking into more acidic late endosomes and lysosomes observed 10–20 min later. , Bis-T-23 promotes dynamin oligomerization, which causes actin polymerization and cross-linking and focal adhesion maturation. , By image analysis, while Bis-T-23 significantly increased F-actin content in cultured podocytes, polymer-drug conjugates did not (Figure S6), likely due to the low dynamic range of this method. Therefore, we sought to develop a more high-throughput method of evaluating Bis-T-23 delivery in cultured podocytes.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…As early as 20–30 min, fluorescently labeled PBA copolymers were mostly internalized (Figure A) and colocalized with LysoTracker, a marker of lysosomes (Figure B). This is consistent with other studies reporting that polycationic materials rapidly traffic into acidic compartments as early as 5 min, with greater trafficking into more acidic late endosomes and lysosomes observed 10–20 min later. , Bis-T-23 promotes dynamin oligomerization, which causes actin polymerization and cross-linking and focal adhesion maturation. , By image analysis, while Bis-T-23 significantly increased F-actin content in cultured podocytes, polymer-drug conjugates did not (Figure S6), likely due to the low dynamic range of this method. Therefore, we sought to develop a more high-throughput method of evaluating Bis-T-23 delivery in cultured podocytes.…”
supporting
confidence: 90%
“…This is consistent with other studies reporting that polycationic materials rapidly traffic into acidic compartments as early as 5 min, with greater trafficking into more acidic late endosomes and lysosomes observed 10–20 min later. 27, 28 Bis-T-23 promotes dynamin oligomerization, which causes actin polymerization and crosslinking and focal adhesion maturation. 7, 2931 By image analysis, while Bis-T-23 significantly increased F-actin content in cultured podocytes, polymer-drug conjugates did not (Figure S6), likely due to the low dynamic range of this method.…”
mentioning
confidence: 99%
“…A recent report used both fluorescent microscopy and a novel organelle tagging technique to follow polyplexes through the uptake and trafficking process [48]. This study showed rapid passage through EE and LE compartments and accumulation in lysosomes.…”
Section: Trafficking Of Oligonucleotides Associated With Other Nanoparticlesmentioning
confidence: 89%
“…Thus, these results support the use of these technologies as a complementary tool for bioprocess characterization and diagnosis at nanometric range (Ping‐Jie et al ., ; Reitan et al ., ; Pike et al ., ). For instance, Manders' overlap coefficient has been recently used to track the presence of siRNA/PEI complexes in endocytic vesicles (Lazebnik & Pack ). Compared to other quantitative techniques, quantitative colocalization is time consuming and requires technical expertise.…”
Section: Discussionmentioning
confidence: 99%